Carotid Occlusion Accentuates Aortic Stenosis and Cardiac Remodeling With Preserved Systolic Function in LDL Receptor-Deficient Mice - Liu, Yandong; Cai, Jiawei; Qu, Lefeng (Frontiers in Physiology, 2021)
Background. Carotid atherosclerotic disease is associated with aortic stenosis and reduced cardiac function. The causality between carotid and cardiac pathologies is unknown. We aim to explore the effects of carotid stenosis or occlusion on cardiac pathology and function. Methods and Results. We produced carotid obstruction or stenosis in 36 atherogenic mice with 150-μm or 300-μm tandem surgery or sham surgery. The structure and function of the heart were assessed by histology and animal ultrasound. The 150-μm group had larger plaque burden and thicker valve leaflets in the aortic root than did the control group. Also, the two surgery groups had thicker left ventricular posterior wall and smaller internal diameter compared with controls. Increased myocardial fibrosis was also found in the 50-μm group compared with controls, although the surgery groups had preserved systolic function compared with that of controls. Conclusions. In a mouse model, carotid occlusion accentuated the formation of aortic stenosis and promoted ventricular remodeling without impairing systolic function. Carotid atherosclerotic plaque may be a pathogenic factor for aortic stenosis and ventricular remodeling.